2002
DOI: 10.3171/jns.2002.97.2.0272
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acids in human cerebrospinal fluid following subarachnoid hemorrhage and their potential role in vasospasm: a preliminary observation

Abstract: Following SAH, all FFAs are initially elevated. A secondary elevation occurs between 8 and 10 days after SAH. This study provides preliminary evidence of FFA elevation following SAH and of a potential role for FFAs in SAH-induced vasospasm. A prospective study is warranted to determine if CSF concentrations of FFAs are predictive of vasospasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 64 publications
3
29
0
Order By: Relevance
“…This is consistent with increased lipolysis due to hypo-insulinaemia [45], but could also be explained by the increased stress response as higher cortisol levels correlated with higher FFA levels and, in general, an increased stress reaction is accompanied by lipolysis with a subsequent increase in FFA levels [46]. Previous studies reported similar observations, with increased FFA levels in cerebral spinal fluid of patients with aneurysmal SAH or with traumatic brain injury [47,48]. The relationship between FFA and insulin appears to be complex [49].…”
Section: Discussionsupporting
confidence: 73%
“…This is consistent with increased lipolysis due to hypo-insulinaemia [45], but could also be explained by the increased stress response as higher cortisol levels correlated with higher FFA levels and, in general, an increased stress reaction is accompanied by lipolysis with a subsequent increase in FFA levels [46]. Previous studies reported similar observations, with increased FFA levels in cerebral spinal fluid of patients with aneurysmal SAH or with traumatic brain injury [47,48]. The relationship between FFA and insulin appears to be complex [49].…”
Section: Discussionsupporting
confidence: 73%
“…[25][26][27][28][29] Both negative nitrogen balance and free fatty acid production have been reported to be associated with vasospasm after SAH. 15,30 Our analysis found an additional finding of a strong inverse relationship between prealbumin, a nonspecific marker of protein catabolism, and hsCRP. A more comprehensive measurement of both protein catabolism and lipid peroxidation with assessments of nitrogen balance and free fatty acid production will lead to a better understanding of the impact of hypermetabolism on DCI.…”
Section: Discussionmentioning
confidence: 81%
“…However, in studies of Alzheimer (33) and Parkinson (34) diseases, neither free nor acyl-carnitine levels significantly correlate with disease. Free fatty acids were shown to increase in patients with traumatic brain injury (35), stroke (36), and subarachnoid hemorrhage (37), yet a decrease in fatty acid concentrations was demonstrated in multiple sclerosis (38) and Alzheimer disease (39).…”
Section: Discussionmentioning
confidence: 99%